2022
DOI: 10.1021/acs.joc.2c01486
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Generation of Acylketene Intermediates via Nitrogen Extrusion

Abstract: A flow chemistry process for the generation and use of acylketene precursors through extrusion of nitrogen gas is reported. Key to the development of a suitable continuous protocol is the balance of reaction concentration against pressure in the flow reactor. The resulting process enables access to intercepted acylketene scaffolds using volatile amine nucleophiles and has been demonstrated on the gram scale. Thermal gravimetric analysis was used to guide the temperature set point of the reactor coils for a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In 2022, Browne and co-workers 22 reported a flow protocol for the generation of acylketene precursors. After the development of a library, the authors also demonstrated the generation and combination of two intermediates via nitrogen extrusion (Scheme 7A), synthesizing an isocyanate in situ through CR.…”
mentioning
confidence: 99%
“…In 2022, Browne and co-workers 22 reported a flow protocol for the generation of acylketene precursors. After the development of a library, the authors also demonstrated the generation and combination of two intermediates via nitrogen extrusion (Scheme 7A), synthesizing an isocyanate in situ through CR.…”
mentioning
confidence: 99%